PKM WORKSHOP MANAJEMEN DAN ADMINISTRASI MUHAMMADIYAH PIMPINAN DAERAH PADANGSIDIMPUAN - Tuah, Sahlan; Hamid Marpaung, Paisal (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The problem with these branches is that the organization has not been well organized, the administrative activities have not been good, to make invitations must go to the rental because the management does not have the ability to operate a computer. This activity aims to improve the ability of partners in managing the organization, increase the ability in the preparation of branch administration, especially in the preparation of reports on the activities of the Muhammadiyah branch, increase the number of administrators who have the ability to use computers to assist in making branch documents. This activity is carried out by the method of discussion of problem solving, management training, administrative preparation, use of computers, mentoring and evaluation. Comprehensive assistance to the management of Muhammadiyah branches through assistance in managing organizational management, administration and the use of computers to assist administrative activities.